2015
DOI: 10.1177/1040638715574768
|View full text |Cite
|
Sign up to set email alerts
|

Detection of African swine fever, classical swine fever, and foot-and-mouth disease viruses in swine oral fluids by multiplex reverse transcription real-time polymerase chain reaction

Abstract: Abstract. African swine fever (ASF), classical swine fever (CSF), and foot-and-mouth disease (FMD) are highly contagious animal diseases of significant economic importance. Pigs infected with ASF and CSF viruses (ASFV and CSFV) develop clinical signs that may be indistinguishable from other diseases. Likewise, various causes of vesicular disease can mimic clinical signs caused by the FMD virus (FMDV). Early detection is critical to limiting the impact and spread of these disease outbreaks, and the ability to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 26 publications
3
46
0
Order By: Relevance
“…A variety of different specimens were submitted for PDCoV testing by real time RT-PCR. Real time RT-PCR is a valuable tool for detecting pathogens, and more recently, oral fluids have been used to screen for a variety of pathogens, including porcine reproductive and respiratory syndrome virus, influenza A virus, African swine fever, classical swine fever, and foot-and-mouth disease viruses (Detmer et al, 2011;Olsen et al, 2013;Grau et al, 2015). While the previous viruses are shed in oral fluids, PDCoV is an enteric pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of different specimens were submitted for PDCoV testing by real time RT-PCR. Real time RT-PCR is a valuable tool for detecting pathogens, and more recently, oral fluids have been used to screen for a variety of pathogens, including porcine reproductive and respiratory syndrome virus, influenza A virus, African swine fever, classical swine fever, and foot-and-mouth disease viruses (Detmer et al, 2011;Olsen et al, 2013;Grau et al, 2015). While the previous viruses are shed in oral fluids, PDCoV is an enteric pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar approach this has been tested in wild boar by Mouchantat et al [5] but a sound evaluation of this non-invasive sampling methodology was not possible due to an unexpected mild course of the experimental infection. The results obtained later by Grau et al [6] showed the feasibility of using the similar conventional rope sampling technique for CSFV genome detection but leaving out the “baiting component” essential for extensive production systems or wild boar sampling. In addition, focusing on the analytical sensitivity of the multiplex RTqPCR, this study did not deliver comparative values for blood samples and the different oral fluid samples over the course of infection.…”
Section: Discussionmentioning
confidence: 99%
“…For classical swine fever (CSF), due to the unexpected mild course of the infection during the experimental study on CSF in wild boar, detailed insights into the suitability of the sampling technique for early detection could not be obtained [5] and remained therefore speculative. The approach of non-invasive sampling for TADs was later picked up by Grau et al [6] successfully detecting the shedding of viral genome of FMDV, ASFV and CSFV in oral fluids collected by the conventional chewing rope technique from infected animals using a multiplex RTqPCR. With CSF remaining one of the most relevant TADs for the pig sector at global level with dramatic socio-economic consequences for producers and other value chain stakeholders [7], the need for additional tools to improve field level disease information in the domestic pig population remains pertinent.…”
Section: Introductionmentioning
confidence: 99%
“…In a field setting, diseased animals may represent only a portion of the population in a particular pen of animals [9,10]. Available information from a study on pigs experimentally infected with ASF, CSF, or FMD show that infected animals were observed chewing on ropes until severe clinical signs developed, concurrent with or after virus was detectable in OF samples [11]. Regarding the timeliness of rope sampling relative to shedding of virus, it is important to note that for all three diseases considered in this evaluation, the incubation and infectious periods vary depending on the strain of virus and its virulence [12].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the timeliness of rope sampling relative to shedding of virus, it is important to note that for all three diseases considered in this evaluation, the incubation and infectious periods vary depending on the strain of virus and its virulence [12]. From laboratory studies, ASF and FMD are detectable in OF samples before presentation of clinical signs and often concurrent to pyrexia [7,11,13,14]. Detectable levels of CSF virus appear in OF samples at the same time or after presentation of clinical signs [11,15,16].…”
Section: Introductionmentioning
confidence: 99%